PERENCANAAN STRATEGIK PRODUK HORTIKULTURA DI AGRIBUSINESS DEVELOPMENT CENTRE IPB - Ramadini, Fadila; Sa’id, Endang Gumbira; Retnaningsih, Retnaningsih (Forum Agribisnis, 2014)
Agribusiness Development Center (ADC) is farmers support institution to produce and distribute top grade horticulture products. The purpose of this study is to formulate strategic planning for ADC. The methods used are internal and external factors analysis, IE matrix, SWOT and QSPM. The result shows five strategies prioritized as follows: expanding Greater Jakarta market, increasing organic products yield, collaborating with research institutes, increasing promotion and adding new distribution channels.